Winchester, Jefferson County - Bertels, Allison (Kansas State University, The Chapman Center for Rural Studies, 2011)
Today, the town of Winchester in Jefferson County, Kansas is small and quiet. But beneath this exterior lies a history rooted deeply in family stories, connections with the railroad and a famous native son.
Allison Bertels, “Winchester, Jefferson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/60.
Keywords: Winchester; Jefferson County; Fort Leavenworth- Fort Riley Military Trail; Atchison; John Steuart Curry; Topeka